Development of a portable electrical impedance spectrometer for the analysis and characterization of blood tissue - Lexequías, Christian (2021)
Using an Analog Discovery 2 as the basis for the development of an electrical impedance spectroscopy (EIS) kit and the adaptation of the Accu-Chek®test strips as a working electrode to perform readings on samples of human blood tissue, it is possible to obtain the corresponding Nyquist spectra for the mentioned tissue. These results indicate a possible correspondence in the electrical impedance signal observed in people with a hemoglobin amount of 14.8 g/dL, 14.7 g/dL, 14.6 g/dL and 13.7 g/dL. It was also possible to simulate with the data obtained the probable graph of a person with 12.7 g/dL of hemoglobin in blood, which corresponds to a patient with anemia. This article analyzes the viability of developing a new less invasive diagnostic method for anemia disease, which is taking place in the Biophysics Laboratory of the Faculty of Physical Sciences - UNMSM.